Graphene Nanobeacons with High‐Affinity Pockets for Combined, Selective, and Effective Decontamination and Reagentless Detection of Heavy Metals (Small 33/2022). Issue 33 (18th August 2022) - Panáček, David; Zdražil, Lukáš; Langer, Michal; Šedajová, Veronika; Baďura, Zdeněk; Zoppellaro, Georgio; Yang, Qiuyue; Nguyen, Emily P.; Álvarez‐Diduk, Ruslan; Hrubý, Vítězslav; Kolařík, Jan; Chalmpes, Nikolaos; et al.
Abstract : Heavy Metal Detection In article number 2201003 by Aristides Bakandritsos, Michal Otyepka, and co‐workers, recyclable fluorescent nanographenes with high‐affinity pockets for toxic metals enable selective and highly effective decontamination of natural water and quality monitoring with sub‐nanomolar sensitivity for lead and cadmium via photoluminescence quenching or optical lateral‐flow sensors.